Receiving GSM Broadcast Channels with an Ultra-Low Power Sub-GHz Transceiver - Erhardt, Stefan; Weigel, Robert; Kölpin, Alexander (European Microwave Conference, 2017)
Mobile phone front-end and baseband modules are hard to obtain on the market for end customers. Thus, software defined radios are widely used in research and development, enabling many opportunities for digital signal processing. In this publication a novel option to receive GSM signals is suggested by using an ultra-low power Sub-GHz transceiver in a legacy mode. The device outputs raw demodulated bits while the signal processing is realized in software. The functionality is proven and quantified by measurements.